Total evidence phylogenetic analysis and reclassification of Euschistus Dallas within Carpocorini (Hemiptera: Pentatomidae: Pentatominae). (30th December 2016) - BIANCHI, FILIPE M.; DEPRÁ, MARÍNDIA; FERRARI, AUGUSTO; GRAZIA, JOCELIA; VALENTE, VERA L. S.; CAMPOS, LUIZ A.
Abstract: Robust phylogenetic hypotheses have become key for studies addressing the evolutionary biology and ecology of various groups of organisms. In the species‐rich heteropteran superfamily Pentatomoidea, phylogenies at lower taxonomic levels are still scarce and mostly employ exclusively morphological data. In this study, we conducted a total evidence phylogeny focusing on the tribe Carpocorini (Pentatomidae), using morphological data and four DNA markers (COI, Cytb, 16S and 28S rDNA; ∼2330 bp; 32 taxa) in order to investigate the relationships within Euschistus Dallas, one of the most speciose pentatomid genera, and between Euschistus and related genera. Our hypotheses generated by maximum likelihood and Bayesian inference show that the current taxonomic composition and classification of Euschistus and allied genera are in need of revision. Euschistus was recovered as nonmonophyletic, with the subgenera forming four independent lineages: Euschistus ( Euschistus ) and Euschistus ( Lycipta ) Stål are sister groups; Euschistus ( Euschistomorphus ) Jensen‐Haarup is more closely related to Dichelops Spinola and Agroecus Dallas; and Mitripus Rolston is divided into two clades closely related to Sibaria Stål and Ladeaschistus Rolston. We chose not to change the classification of E. ( Euschistomorphus ) until further data become available, and propose to split Euschistus into three genera with the exclusion of Euschistus ( Mitripus ) and all of its species. Here we elevate Mitripus to genus rank to include M. acutus comb.n., M. convergens comb.n. and M. legionarius comb.n., and propose Adustonotus Bianchigen.n. to include A. anticus comb.n., A. latus comb.n., A. tauricornis comb.n., A. grandis comb.n., A. hansi comb.n., A. paranticus comb.n., A. irroratus comb.n. and A. saramagoi comb.n. We also provide identification keys to the genera Adustonotus gen.n., Ladeaschistus, Mitripus n. rank and Sibaria, here defined as the Mitripus genus group, and to the species of Mitripus and Adustonotus gen.n. Our results provide insights into the current status of the classification of the Pentatomidae, suggesting the need for phylogenetic analyses at different taxonomic levels within stink bugs. This published work has been registered in ZooBank, http://zoobank.org/urn:lsid:zoobank.org:pub:E09D2675‐0F2B‐4AAE‐9837‐257E0B18BC52 .